New records of phytoplankton for Bangladesh. 8. Trachelomonas Ehr. (Euglenophyceae) (Bangladesh Journal of Botany, 2008)
Investigation of pelagic plankton communities from some freshwater ponds of Pirojpur and Barisal districts revealed the presence of 17 species under the genus Trachelomonas Ehr. for the first time in Bangladesh. Key words: Phytoplankton, Trachelomonas, New records, Ponds, Bangladesh doi:10.3329/bjb.v37i2.1719 Bangladesh J. Bot. 37(2): 133-139, 2008 (December)